Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.4049/jimmunol.165.12.7078
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Exogenous Antigen in Priming the Human CD8+ T Cell Response: Lessons from the EBV Nuclear Antigen EBNA1

Abstract: Mouse models suggest that the processing of exogenous Ag by dendritic cells can be important for priming the CD8+ CTL response. To study the situation in humans, we have exploited the CTL response to EBV infection. In this context EBV expresses eight latent proteins, of which EBV-encoded nuclear Ag (EBNA) 3A, 3B, and 3C appear to be immunodominant for CTL responses, whereas another nuclear Ag, EBNA1, which is completely protected from endogenous presentation via the MHC class I pathway, is thought to induce re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
94
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 41 publications
5
94
1
1
Order By: Relevance
“…Similar observations have been made in many different viral infections, including vaccinia virus [5, 77,78], influenza virus [78] and Epstein-Barr virus (EBV) [79,80] infection. In the case of EBV-induced Burkitt's lymphoma, a glycine-alanine repeat domain in the EBNA1 protein, required to establish viral latency, completely blocks proteasome-dependent MHC class I processing in EBNA1-expressing cells.…”
Section: Evidence For Cross-priming In Infectious Diseasessupporting
confidence: 75%
See 2 more Smart Citations
“…Similar observations have been made in many different viral infections, including vaccinia virus [5, 77,78], influenza virus [78] and Epstein-Barr virus (EBV) [79,80] infection. In the case of EBV-induced Burkitt's lymphoma, a glycine-alanine repeat domain in the EBNA1 protein, required to establish viral latency, completely blocks proteasome-dependent MHC class I processing in EBNA1-expressing cells.…”
Section: Evidence For Cross-priming In Infectious Diseasessupporting
confidence: 75%
“…In the case of EBV-induced Burkitt's lymphoma, a glycine-alanine repeat domain in the EBNA1 protein, required to establish viral latency, completely blocks proteasome-dependent MHC class I processing in EBNA1-expressing cells. Nonetheless EBNA1-specific CTL can be readily detected in EBV-infected individuals [79,80]. This can best be explained by crosspresentation and cross-priming.…”
Section: Evidence For Cross-priming In Infectious Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…EBNA-1 is an immunodominant latent target of EBVspecific CD4 1 T cells [19,20]. Although it has been described in the past to escape from recognition by CD8 1 T cells due to Gly/Ala repeated domains preventing proteasome-dependent processing for presentation on MHC class I [21], more recent studies revealed the existence of EBNA-1-specific CD8 1 T cells [15,22,23]. Moreover, detection of anti-EBNA IgG in seropositive individuals suggests need for CD4 help.…”
mentioning
confidence: 99%
“…Or, ce n'est pas le cas, car il est très difficile de détecter cette protéine EBNA1 dans les cellules infectées. De plus, une réponse T cytotoxique peut être induite contre des peptides d'EBNA1 par un mécanisme appelé cross presentation [4]. Ces cellules T peuvent reconnaître des molécules du CMH I chargées en peptides exogènes provenant de la protéine EBNA1 mais pas des molécules du CMH I présentant des peptides endogènes.…”
unclassified